INOVASI BAHAN AJAR PAI AUDIO VISUAL BERBASIS YOUTUBE UNTUK MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK - Nora Fauliana (Postgraduate Program UIN Sultanah Nahrasiyah Lhokseumawe, 2025)
Innovation in Islamic Religious Education (PAI) learning is an urgent need in the digital era to address low student motivation caused by monotonous conventional methods. This study aims to develop audiovisual-based PAI teaching materials through the YouTube platform as a more engaging and interactive learning solution tailored to the digital generation. Using the Research and Development (R&D) method, the research was conducted at SMP Al-Qur'an Ar-Raudhah involving PAI teachers and 24 eighth-grade students. The development process included needs identification, educational video content design, expert validation, and field testing. Results show that the use of YouTube learning videos increased student motivation by 25% and facilitated understanding of complex topics such as fiqh and Islamic cultural history. Most students (83%) demonstrated high enthusiasm for video-based learning. However, challenges such as limited internet access and the need to select content aligned with Islamic values remain. Overall, YouTube-based PAI teaching materials proved effective as an adaptive learning medium that bridges the gap between conventional methods and current student needs, with strong potential for broader implementation in religious education.